If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 15 = x + -20 Reorder the terms: 15 + 5x = x + -20 Reorder the terms: 15 + 5x = -20 + x Solving 15 + 5x = -20 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 15 + 5x + -1x = -20 + x + -1x Combine like terms: 5x + -1x = 4x 15 + 4x = -20 + x + -1x Combine like terms: x + -1x = 0 15 + 4x = -20 + 0 15 + 4x = -20 Add '-15' to each side of the equation. 15 + -15 + 4x = -20 + -15 Combine like terms: 15 + -15 = 0 0 + 4x = -20 + -15 4x = -20 + -15 Combine like terms: -20 + -15 = -35 4x = -35 Divide each side by '4'. x = -8.75 Simplifying x = -8.75
| 9xsquared-21=0 | | X-6-x-4=10-c | | -104=5x-3(5x+8) | | .5f=c+6u | | -3+5(b+4)+4(b+3)=2 | | x^(-3/5)=27 | | -7x-6(2x+5)=84 | | 3(n+3)+-2n+2(n+4)=65 | | 8-5x=2c-9x | | 16l=4c^2+9 | | -x/6=5-8 | | 12(t+2)+-7t+-8=6 | | 5x=48+x | | 6sec(x)+8=-4 | | 38.00=0.12m+8 | | -3(-6v+6)-v=2(v-8)-7 | | -5/8x-7.5=7.5 | | -5y=6-4y | | 12(n+1)+-11n+2(n+1)=56 | | 7-3(19z-17)=-4(-2z+18) | | 2g=3g-9 | | -5/8x=0 | | -15+3(b+2)+4(b+1)=2 | | 7h+2=8h-6 | | -9+8b=-b | | 9h-7=3+7h | | h=-16t^2+38t+15 | | 3.7+13.4h=12.94+14.1h | | x/10=10*x | | 2cos(3x)= | | 8x^3-126x-4=0 | | 4(y+6)=-2(4y-9)+2y |